Building value: The role of trademarks for economic development - Fredrik Erixon; Maria Salfi (European Centre for International Political Economy (ECIPE), 2015)
Investment in brands drives the allocation of resources in our economy. It increases competition, pushes firms to innovate, and decreases asymmetries in the market leading to a higher level of economic development. Investment in brands and intangibles has seen an increase in the last fifteen years, especially in advanced economies such as the EU and the US. The US is a pioneer when we talk about investment in brands, whereas the EU is still investing a higher share of GDP in tangible assets. Differences within the European Union are also significant. Size seems to matter. Larger economies usually invest less in brands, whereas relatively smaller economies invest more. Moreover, smaller economies tend to "spend" more on branding compared to bigger ones. However, on average, the economies taken in our sample (EU27 plus Norway and US) show that they correlate positively with investment in brands. The econometric results show a positive and significant correlation between investment in brands and GDP per capita. Nonetheless, each country's economic characteristics influence the role that brands play in the economy. Examples analysed in this policy brief are Germany and Sweden, where GDP per capita and investment in brands are negatively correlated, and Norway and the US, where correlation between the variables is rather positive.
Keywords: 330; Investitionspolitik; Markenartikel; Markenrecht; Immaterielle Güter; Bruttoinlandsprodukt; Vergleich; Deutschland; Schweden; Norwegen; USA